An audit of referring patterns for cancer patients to the Palliative Care Unit in 2 Military Hospital, by means of a retrospective evaluation of the percentage of referrals adhering to a given standard, and evaluation of possible barriers - Engelbrecht, Mari (Department of Public Health and Family Medicine, 2014)
Includes bibliographical references.